2022
DOI: 10.48208/headachemed.2022.6
|View full text |Cite
|
Sign up to set email alerts
|

New precipitating factors for migraine during Covid-19 pandemic lockdown

Abstract: Background: Lock down caused sudden lifestyle changes and represented a massive impact on human health. We aimed to report new migraine headache precipitating factors due to lifestyle changes during coronavirus disease 2019 (COVID-19) Pandemic lockdown. Methods: This cross-sectional survey included patients diagnosed with migraine based on The International Classification of Headache Disorders, 3rd edition (ICDH-3). During the lockdown, we submitted an online self-reported web-based questionnaire to patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that Covid-19 can induce temporary, or sometimes complete smell loss [ 81 ]. In addition, during lockdown, smells were precipitating factors of migraine attacks even more than before the pandemic [ 82 , 83 ], and higher post-infection olfactory symptoms were found in migraine Covid-19 survivors as compared to non-migraine survivors [ 84 ]. None of the patients included here had Covid-19, or had recovered from Covid-19 in the two weeks prior to testing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Covid-19 can induce temporary, or sometimes complete smell loss [ 81 ]. In addition, during lockdown, smells were precipitating factors of migraine attacks even more than before the pandemic [ 82 , 83 ], and higher post-infection olfactory symptoms were found in migraine Covid-19 survivors as compared to non-migraine survivors [ 84 ]. None of the patients included here had Covid-19, or had recovered from Covid-19 in the two weeks prior to testing.…”
Section: Discussionmentioning
confidence: 99%
“…They describe significant changes in how such factors would act before and after the Covid-19 pandemic. 26 Interestingly, the cultural relationship with one of the most cited migraine triggers -a strong or particular type of smell -was commented on during the lockdown. The reason that odors are indicated as the main trigger of migraine attacks is interpreted as increased consumption and exposure to incense smoke and the use of Arab perfumes by the population.…”
mentioning
confidence: 99%